2016
DOI: 10.1137/140989443
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Feedback Synthesis and Minimal Time Function for the Bioremediation of Water Resources with Two Patches

Abstract: This paper studies the bioremediation, in minimal time, of a water resource or reservoir using a single continuous bioreactor. The bioreactor is connected to two pumps, at different locations in the reservoir, that pump polluted water and inject back sufficiently clean water with the same flow rate. This leads to a minimal-time optimal control problem where the control variables are related to the inflow rates of both pumps. We obtain a nonconvex problem for which it is not possible to directly prove the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Moreover, one can check that the usual Monod law given in (2.2) is a concave function, that leads to the following expression of the function S eq R : S eq R (S a ) = K 2 s + K s S a − K s . In [13], it is also shown that this feedback is robust w.r.t. the approximation of the quasi-steady state of the dynamics (2.1a) and (2.1b).…”
Section: Ode-based Model and Related Feedback Strategymentioning
confidence: 97%
“…Moreover, one can check that the usual Monod law given in (2.2) is a concave function, that leads to the following expression of the function S eq R : S eq R (S a ) = K 2 s + K s S a − K s . In [13], it is also shown that this feedback is robust w.r.t. the approximation of the quasi-steady state of the dynamics (2.1a) and (2.1b).…”
Section: Ode-based Model and Related Feedback Strategymentioning
confidence: 97%
“…u 2 . As we shall see later in the analysis of the minimal time problem, the consideration of a second control u 2 changes significantly the optimal control problem, compared to the former works [3,9]). PROOF.…”
Section: Assumptions and Preliminariesmentioning
confidence: 99%
“…Therefore, one cannot guarantee the existence of an optimal trajectory with the usual Filippov's Theorem. Nevertheless, it exists among relaxed controls, which amounts to consider controls (u a 1 , u b 1 , p, u 2 ) in U 2 with the dynamicsṡ = pF (s, u a 1 ) + (1 − p)F (s, u b 1 ) + G(s)u 2 as we did in [9].…”
Section: Lemmamentioning
confidence: 99%
“…The principle of the above proposition and its proof, is to establish that the optimal feedback S → S opt T (S) is the one that makes the time derivative of S the most negative at any time in (6). Observe that a necessary condition for a feedback S opt T (S) to be optimal is to verify…”
Section: Proposition 22 the Optimal Feedback Fulfillsmentioning
confidence: 99%